Impact of air pollution and population vulnerability on cancer mortality in the United States: A scoping review - Nan Ji; Shanada Monestime; Lori Rosman; Chijindu Nwakama; Brittney Nichols; Ana M. Rule; Kirsten Koehler; Lesliam Quirós-Alcalá (Science of The Total Environment, 2026)

Hazardous Environmental Pollutants and Cancer Disparities: A Systematic Review on the Consideration of Race and Ethnicity in Environmental Epidemiology Research - Molly E. Schwalb; Kala Visvanathan; Avonne E. Connor; Christine Marie George; Ana M. Rule; Eliseo Guallar; Miranda R. Jones (Current Environmental Health Reports, 2025)

Swine production intensity and swine-specific fecal contamination of household surfaces at residences of industrial livestock operation workers and community residents, North Carolina, USA - Kathleen M. Kurowski; Nora Pisanic; Kristoffer Spicer; Kate Kruczynski; Carolyn Gigot; Devon J. Hall; Devon J. Hall; Kyle T. Aune; Bonita Salmerón; Ana M. Rule; Christopher D. Heaney (Science of The Total Environment, 2025)

Calibration of indoor temperature and relative humidity readings in the PurpleAir monitor - Kyle T. Aune; Megan Wilks; Timothy Green; Ana M. Rule; Meredith McCormack; Nadia N. Hansel; Nirupama Putcha; Gregory Kirk; Sarath Raju; Kirsten Koehler (Environmental Monitoring and Assessment, 2025)

Use of electron microscopy to determine presence of coal dust in a neighborhood bordering an open-air coal terminal in Curtis Bay, Baltimore, Maryland, USA - Matthew A. Aubourg; Kenneth J.T. Livi; Gregory G. Sawtell; Carlos C. Sanchez-Gonzalez; Nicholas J. Spada; Russell R. Dickerson; Wen-An Chiou; Conchita Kamanzi; Gurumurthy Ramachandran; Ana M. Rule; Christopher D. Heaney (Science of The Total Environment, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Manufacturing practices as potential sources of cadmium and other relevant metals in processed meat products. Risk and nutritional assessment - Pablo Olmedo; Rui Chen; Maria Grau-Perez; Keeve E. Nachman; Fernando Gil; Ana M. Rule; Ana Navas-Acien (Food Control, 2024)

Evaluation of calibration approaches for indoor deployments of PurpleAir monitors - Kirsten Koehler; Megan Wilks; Timothy Green; Ana M. Rule; Misti L. Zamora; Colby Buehler; Abhirup Datta; Drew R. Gentner; Nirupama Putcha; Nadia N. Hansel; Gregory D. Kirk; Sarath Raju; et al. (Atmospheric Environment, 2023)

Exposure to metals among Electronic Nicotine Delivery System (ENDS) users in the PATH study: A longitudinal analysis - Bekir Kaplan; Ana Navas-Acien; Ana M. Rule; Markus Hilpert; Joanna E. Cohen (Environmental Research, 2023)

Evaluation of a water arsenic filter in a participatory intervention to reduce arsenic exposure in American Indian communities: The Strong Heart Water Study - Tracy Zacher; Kelly Endres; Francine Richards; Lisa Bear Robe; Martha Powers; Joseph Yracheta; David Harvey; Lyle G. Best; Reno Red Cloud; Annabelle Black Bear; Steve Ristau; Dean Aurand; et al. (Science of The Total Environment, 2023)

The relationship between the use of electronic nicotine delivery systems (ENDS) and effects on pulmonary immune responses—a literature review - Seok Gyu Han; Fenna CM. Sillé; Jana N. Mihalic; Ana M. Rule (Environmental Research, 2023)

Seasonal and Spatial Variability of PM2.5 Concentration, and Associated Metal(loid) Content in the Toluca Valley, Mexico - Ana Larissa Barbosa-Sánchez; Ciro Márquez-Herrera; Rodolfo Sosa-Echeverria; Raúl Venancio Díaz-Godoy; María Eugenia Gutiérrez-Castillo; Consuelo Escamilla-Núñez; Ana M. Rule; Martha Patricia Sierra-Vargas; Octavio Gamaliel Aztatzi-Aguilar (Bulletin of Environmental Contamination and Toxicology, 2022)

Correction to: Early Cardiovascular Risk in E-Cigarette Users: the Potential Role of Metals - Ana Navas-Acien; Irene Martinez-Morata; Markus Hilpert; Ana Rule; Daichi Shimbo; Nancy J. LoIacono (Current Environmental Health Reports, 2020)

Early Cardiovascular Risk in E-cigarette Users: the Potential Role of Metals - Ana Navas-Acien; Irene Martinez-Morata; Markus Hilpert; Ana Rule; Daichi Shimbo; Nancy J. LoIacono (Current Environmental Health Reports, 2020)

Correction to: A conceptual model to understand the soluble and insoluble Cr species in deliquesced particles - Dinara Konakbayeva; Enoch Kwasi Adotey; Mehdi Amouei Torkmahalleh; Marios M. Fyrillas; Altyngul Zinetullina; Ana M. Rule; Philip K. Hopke (Air Quality, Atmosphere & Health, 2020)

A conceptual model to understand the soluble and insoluble Cr species in deliquesced particles - Dinara Konakbayeva; Enoch Kwasi Adotey; Mehdi Amouei Torkmahalleh; Marios M. Fyrillas; Altyngul Zinetullina; Ana M. Rule; Philip K. Hopke (Air Quality, Atmosphere & Health, 2019)

The Acute Effects of Age and Particulate Matter Exposure on Heart Rate and Heart Rate Variability in Mice - Blake A. Bennett; Ernst W. Spannhake; Ana M. Rule; Patrick N. Breysse; Clarke G. Tankersley (Cardiovascular Toxicology, 2018)

Hydrocarbon Release During Fuel Storage and Transfer at Gas Stations: Environmental and Health Effects - Markus Hilpert; Bernat Adria Mora; Jian Ni; Ana M. Rule; Keeve E. Nachman (Current Environmental Health Reports, 2015)